218 The Impact on Minimally Invasive Urological Cancer Surgery During the Covid-19 Pandemic. (12th October 2021) - Boyle, C; Gallagher, K; Leung, S; Good, D; McNeill, S A; Laird, A
Abstract: Aim: Learned bodies recommended restricted use of, or extensive precautions when using, laparoscopic/robotic surgery during the Covid-19 pandemic. We aimed to determine whether minimally invasive surgery (MIS) in uro-oncology patients was safe for patients and staff. Method: From 16 March to 16 June 2020, patients having MIS in a tertiary referral urology centre were identified from a prospectively collected database. Patient characteristics, operative details and 30-day follow-up for adverse events were recorded including Covid-19 tests and results. Any theatre staff Covid-19 event was traced back 14 days to determine any involvement in these cases. Results: 87 patients were eligible for inclusion (33 robotic prostatectomies, 38 laparoscopic prostatectomies, 11 laparoscopic nephrectomies, 5 robotic nephrectomies). All patients were assessed for symptoms of Covid-19 on the day of theatre. 18(21%) patients had pre-operative screening (all swabs, no CT chest). 46(53%) underwent 14 days pre-operative self-isolation. 38(44%) cases were performed with FFP3 protection. No modification to operating procedure was made for any cases. No patients tested positive for Covid-19 in the 30-day postoperative period. No staff member involved tested positive in the postoperative period. 1 patient tested positive pre-operatively, delaying the operation by 7 weeks. No patients tested positive after the introduction of mandatory screening. Conclusions: Based on our case-series MIS urological surgery appears to be safe for patients and staff, with no increased risk of Covid-19 complications in patients who are asymptomatic pre-operatively. The introduction of mandatory pre-operative swabs for elective patients, and the use of FFP3 protection, did not significantly alter results.